Experimental and numerical studies on seismic behavior of bonded and unbonded prestressed steel reinforced concrete frame beam. (15th July 2018) - Xiong, Xueyu; Yao, Gangfeng; Su, Xiaozu
Highlights: Prestressed steel reinforced concrete frame beams were vertically cyclic-loaded. One specimen had unbonded tendons (UPSRC), the other had bonded tendons (BPSRC). The seismic behavior of the two types was studied experimentally and numerically. The strength and energy-dissipation of the UPSRC was as good as the BPSRC. Prestress friction loss and deformation restoring of UPSRC was superior to BPSRC. Abstract: An experimental study was conducted to investigate the behavior of prestressed steel reinforced concrete (PSRC) frame beams subjected to vertical cyclic loading. Two one-fifth-scale specimens respectively with unbonded (UPSRC) and bonded (BPSRC) tendons were tested. The failure modes, skeleton curves, ductility, deformation restoring capacity and energy dissipation capacity were discussed. Results implied that the PSRC frame beams showed a typical beam hinge failure pattern. The ductility coefficients of UPSRC and BPSRC are 2.91 and 2.84, indicating that prestress tendon form (unbonded/bonded) seems to exhibit little influence on the ductility of PSRC frame beams. The downward deformation restoring capacity of UPSRC was superior to BPSRC and the residual deflection corresponding to service load (260 kN) were respectively −1.2 mm and −3.8 mm. The amount of energy dissipated by UPSRC was equivalent to that by BPSRC under the vertical cyclic loading. Moreover, twenty-six specimens were designed for numerical analysis to investigate the effects of parameters, including the amount of rebar and steel shape, concrete strength, and initial effective prestress, on the vertical seismic performance of PSRC frame beams.